Circular agriculture for sustainable and low-carbon development in the People’s Republic of China - Kimura, Shingo; Chen, Kevin Z.; Gong, Binlei (Asian Development Bank, 2022)
Detailing the environmental impact of the PRC's previous high-growth agricultural policies, it outlines its plan to cut emissions from fertilizers, paddy fields, and livestock to help reach its 2060 carbon neutrality target. Drawing on ADB field studies, it recommends the PRC build institutional capacity, boost private investment, and develop bio-based value chains to create a low-carbon, circular model that helps the rural sector become more prosperous and sustainable.